2015
DOI: 10.1177/2051415814556335
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic abnormalities in patients treated with percutaneous nephrolithotomy

Abstract: Objectives: To assess metabolic abnormalities in patients with percutaneous nephrolithotomy (PCNL) that could pose a risk for stone recurrence. Materials and methods: The data was collected retrospectively on all patients who had PCNL and metabolic studies, between January 2000 and September 2012. Results: There were 144 patients; median age and follow up were 49.5 (15-4) years and 80.2 (16-180) months, respectively. Nearly half of the patients had staghorn calculus. Metabolic abnormalities (MAs) were found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Nandwani GM et al reported hypomagnesiuria in 4.2 % of cases. 18 This was not in concordance with the study.…”
mentioning
confidence: 47%
“…Nandwani GM et al reported hypomagnesiuria in 4.2 % of cases. 18 This was not in concordance with the study.…”
mentioning
confidence: 47%